Forensic Stylistic Analysis on University of Airlangga’s Veterinary Medicine Student’s Suicide Notes - Andini, Riza Saskia; Lorise, Grace; Kurniawan, Salsabila; Panggabean, Erin Yohana; Khansa, Syifa Nadiah; Rangkuti, Rahmadsyah (Titian: Jurnal Ilmu Humaniora, 2023)
Suicide note is the note that left by someone who decided to take their own lives, or commit suicide. The suicide note that left by the University of Airlangga’s student that majoring the Veterinary Medicine Department, CA (21), for her mom and her sibling is the background of this research was made. CA decided to take her own life by poisoning herself with helium gas inside of her car. She left a note, addressed to her mom and her brother and sister. This analysis aims to prove the originality of the notes left and why did CA commit to suicide. The researchers collected the data in the form of photo of the note from the internet and then process it using Linguistics Inquiry and Word Count (LIWC) program. The content of the note is also being examined starting from the greetings, the content, and finally the closings of the notes. The result of the research is the note that left by CA is genuine without being faked or manipulated. Abstrak Catatan bunuh diri adalah catatan yang ditinggalkan oleh seseorang yang memutuskan untuk mengakhiri hidupnya sendiri, atau melakukan bunuh diri. Catatan bunuh diri yang ditinggalkan oleh seorang mahasiswa Universitas Airlangga jurusan Kedokteran Hewan, CA (21), kepada ibunya dan saudara-saudaranya menjadi latar belakang penelitian ini. CA memutuskan untuk mengakhiri hidupnya sendiri dengan meracuni dirinya sendiri menggunakan gas helium di dalam mobilnya. Ia meninggalkan catatan yang ditujukan kepada ibunya serta saudara-saudaranya. Analisis ini bertujuan untuk membuktikan keaslian catatan yang ditinggalkan serta mengapa CA memutuskan untuk bunuh diri. Peneliti mengumpulkan data berupa foto catatan dari internet dan kemudian memprosesnya menggunakan program Linguistics Inquiry and Word Count (LIWC). Isi dari catatan juga diperiksa mulai dari salam pembuka, isi, dan akhir dari catatan tersebut. Hasil dari penelitian ini menunjukkan bahwa catatan yang ditinggalkan oleh CA adalah asli tanpa ada pemalsuan atau manipulasi.